الإحالة الإتساقية في النصوص القرآنية في سورتي البقرة وآل عمران : دراسة تحليلية تركيبية ونصية - سيتي سارا بنت حاج أحمد (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2009)
This research work examines Cohesive Reference at sentence and text levels. It highlights its roles in creating structural cohesion between sentential and textual elements by identifying the semantic and pragmatic functions of the elements. It further mentions the contributions of traditional and modern Arab and western scholars to the study and analysis of Cohesive Reference. The research specifically explores the features of Cohesive Reference identifiable on the sentential and textual levels in the Qur'anic texts by analyzing selected texts from Surah al-baqarah and al-'imran, specifically verses (from 158 to 218 ) of surah al-baqarah, and other verses (from 121 to 180) of al-'imran. Elements of Cohesive Reference in sentences and texts are studied through the application of descriptive and analytic methodology. The thesis eventually concludes that focusing on the elements of cohesive reference assists in comprehending the semantic and pragmatic dimensions of Qur'anic Texts, thus facilitating the identification of the signifying and signified elements in the verses of the Holy Qur'an. The work therefore suggests, among others, that elements of Cohesive Reference at both sentential and textual levels be seriously studied for better understanding of the Qur'anic texts.